Impact of COVID19 pandemic on the incidence of health-care associated Clostridioides difficile infection. (June 2022) - Merchante, Nicolás; Chico, Pablo; Márquez-Saavedra, Esther; Riera, Gerónima; Herrero, Rocío; González-de-la-Aleja, Pilar; Aller, Ana I.; Rodríguez, Juan Carlos; Rodríguez-Fernández, Miguel; Ramos, José Manuel; Trigo-Rodríguez, Marta; Merino, Esperanza
Abstract: Objective: To investigate the impact of COVID19 pandemic on the incidence of health-care associated Clostridioides difficile infection (HA-CDI). Methods: Retrospective study conducted in the Hospital Universitario de Valme (HUV) and the Hospital General Universitario de Alicante (HGUA) in Spain between January 2019 and February 2021. The study period was divided into non-COVID19 period (2019 and months from 2020 to 2021 with ≤30 hospitalized COVID19 patients) and COVID19 period (months from 2020 to 2021 with >30 COVID19 patients). HA-CDI incidence rates (IR) were calculated as the number of new CDI cases per 10.000 occupied bed-days (OBD) and antimicrobial consumption by means of the defined daily dose (DDD) per 1000 OBD. Results: During the COVID19 period, HA-CDI IR in the HUV was 2.6 per 10.000 OBD, which was lower than what was observed during the non-COVID19 period (4.1 per 10.000 OBD; p = 0.1). In the HGUA, HA-CDI IR during COVID19 period was 3.9 per 10.000 OBD, which was not significantly different to the IR observed during the non-COVID19 period (3.7 per 10.000 OBD; p = 0.8). There was a slight increase in the total antibiotic consumption during COVID19 period in both hospitals, with significant increases of certain high-risk antibiotics as cephalosporins. Conclsusions: HA-CDI incidence has not increased during the COVID19 pandemic in two tertiary centers in Spain, in spite of a slightly higher antibiotic consumption during the COVID19 period in both hospitals. These findings suggest that, in the presence of strict infection control measures, hospital antibiotic consumption might have a lower impact than expected on HA-CDI. Highlights: Healthcare-associated CDI incidence has not increase during COVID19 in spite of higher antibiotic consumption. Decreases of hospital-onset healthcare facility-associated CDI incidence in every wave were seen in one center. Strict infection control measures mitigate the impact of hospital antibiotic use.